(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This thesis analyzes the linguistic features of Arabic-origin medical units used in Abu Ali Ibn Sina’s Canon of Medicine. The study focuses on how these medical terms entered the Uzbek language, their semantic shifts, polysemy, homonymy, and contextual usage. Particular attention is given to the role of Arabic borrowings in shaping the historical layers of Uzbek medical terminology.